A ZnCl2‐Catalyzed Knoevenagel Condensation/1, 5‐Hydride Shift/Cyclization Sequence: Synthesis of Novel Spiroisoxazol‐5‐one Tetrahydroquinolines. Issue 13 (22nd August 2016) - Zhao, Tuan; Zhang, Huanrui; Cui, Longchen; Wang, Changxue; Qu, Jingping; Wang, Baomin
Abstract: A concise synthesis of novel spiroisoxazol‐5‐one tetrahydroquinoline derivatives has been developed by an efficient ZnCl2 ‐catalyzed stereoselective Knoevenagel Condensation/1, 5‐hydride shift/cyclization sequence. The reactions are broad in scope and the products could be obtained in good to high yields (up to 97 % yield) with good to excellent diastereoselectivities (up to >95:5 dr). In addition, these products may be converted into novel 5‐hydroxy‐spiroisoxazolines and spiropyrazolones. Abstract : A concise synthesis of novel spiroisoxazol‐5‐one tetrahydroquinoline derivatives has been developed by an efficient ZnCl2 ‐catalyzed stereoselective Knoevenagel condensation/1, 5‐hydride shift/cyclization sequence. The reaction is broad in scope and the products could be obtained in good to high yields (up to 97 % yield) with good to excellent diastereoselectivities (up to >95:5 dr).In addition, the products may be converted into novel 5‐hydroxy‐spiroisoxazolines and spiropyrazolones.